2015
DOI: 10.4209/aaqr.2015.02.0307
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Aerosol Elements over the Inland Tibetan Plateau: Concentration, Seasonality, and Transport

Abstract: Between November 2005 and November 2007, weekly total suspended particle samples were collected at the Nam Co station in the inland Tibetan Plateau (TP). Through inductively coupled plasma mass spectrometry, twenty-nine elements were analyzed and their sources and fluxes were investigated. Mean elemental concentrations were lower than those at the edge of the TP. Some elements, such as Cr, Ni, Cd, and Pb, exhibited high enrichment factors (Cr: 22; Ni: 17; Cd: 23; and Pb: 9), indicating possible anthropogenic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…MD mass was simply derived from one single metallic element mass with a weighting factor (e.g., Al/0.07 and Fe/0.04) in some studies (Sciare et al., 2005; Zhao et al., 2013). However, the proportions of metallic elements in MD vary greatly for different regions and particle sizes (Kang et al., 2016; Wang et al., 2016; Zhang et al., 2003). Thus, the MD mass calculation by a single metallic element suffers from large uncertainty.…”
Section: Atmospheric Aerosol Chemical Compositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…MD mass was simply derived from one single metallic element mass with a weighting factor (e.g., Al/0.07 and Fe/0.04) in some studies (Sciare et al., 2005; Zhao et al., 2013). However, the proportions of metallic elements in MD vary greatly for different regions and particle sizes (Kang et al., 2016; Wang et al., 2016; Zhang et al., 2003). Thus, the MD mass calculation by a single metallic element suffers from large uncertainty.…”
Section: Atmospheric Aerosol Chemical Compositionsmentioning
confidence: 99%
“…Waliguan, Gongga, Lhasa, and Mt. Yulong (Cong et al., 2015; Kang et al., 2016; Wan et al., 2016; Xu et al., 2020; Zhang et al., 2001, 2012; Zhao et al., 2013). Chemical characterization of submicron aerosols has also been carried out by using aerosol mass spectrometer at a few sites such as Menyuan (Du et al., 2015), Mt.…”
Section: Introductionmentioning
confidence: 99%
“…The TP is surrounded by various sources of pollutants. Over the south of the TP, previous studies have suggested that southern Asia was the main source of pollutants transported to the plateau (e.g., Cong et al, 2009Cong et al, , 2015aKopacz et al, 2011;Lu et al, 2012;Zhao et al, 2013;Wang et al, 2015;Zhang et al, 2015;Kang et al, 2016Kang et al, , 2019Chen et al, 2018). A huge blanket or layer of "haze" is composed of light-absorbing carbonaceous aerosol particles that often erupts in the pre-monsoon season over southern Asia and has a significant influence on the plateau (e.g., Prasad and Singh, 2007;Engling and Gelencser, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Gongga and the crust, respectively. It has been documented that the element with the EF value larger than 10 is considered enriched (Deng et al, 2011;Kang, Chen, et al, 2016). When using the data of the La/Al ratio from UCC, the calculated EF for La in the PM 2.5 samples was 55 ± 12, suggesting a large enrichment of La relative to UCC.…”
Section: 1029/2019jd031327mentioning
confidence: 98%